Pengaruh Pemberian Zat Pengatur Tumbuh Air Kelapa Terhadap Perkecambahan Jengkol (Pithecellobium jiringa) - Martiani, Rani; Ananto, Ananto; Sari, Wilna; Putri, Santi Diana (JURNAL AGROPLASMA, 2024)
The research on the Response of Natural Growth Regulator Coconut Water on the Germination of Jengkol (Pithecellobium jiringa) was conducted from February to April 2022 in Nagari Pematang Panjang, Sijunjung District, Sijunjung Regency. The aim of this study was to examine the effect of coconut water on the germination of jengkol and to determine the optimal dosage of coconut water for jengkol seed germination. The research utilized a completely randomized design (CRD) with five treatment levels: B0 (Control), B1 (25% Coconut Water), B2 (50% Coconut Water), B3 (75% Coconut Water), and B4 (100% Coconut Water). Data were analyzed using the F-test at a 5% significance level, and if the calculated F value was greater than the table F value at 5%, Duncan's New Multiple Range Test (DNMRT) was applied at the same significance level. The observed variables included the time of radicle emergence, time of epicotyl emergence, time of first leaf emergence, plant height, and root length. The results showed an interaction between the doses of coconut water applied to the jengkol seeds, with the 50% coconut water treatment yielding the best results for jengkol germination. Keywords: natural growth regulator, germination, jengkol